Dreadful desires : the uses of love in neoliberal China - Zhang, Charlie Yi, 1979- (Thought in the act., 2022)
"Dreadful Desires investigates how love is orchestrated as an apparatus of sentiments integrating individual subject making with exploitative policies to serve collective interests of the Chinese state and transnational capital. Drawing upon discursive analysis, empirical data, and ethnographic fieldwork as well as popular culture texts, Charlie Yi Zhang investigates how love is orchestrated as an apparatus of sentiments through the systems of gender, class, and sexuality that integrates individual subject-making with regulation of population to serve collective interests of the Chinese state and transnational capital. Zhang deciphers the ways in which love is projected as a cluster of desirable potentialities, such as private property ownership, upward mobility, and endurable heteronormative intimacy, that generate enduring attachment shaping people's subjectivities. These love-impelled individual subjectivities are aligned with gendered, classed, and sexualized regulation of population by the state to reproduce cheap labor that has fueled China's marketization and reintegration with the global economy"--